Hydraulic conductivity fields: Gaussian or not?. Issue 8 (5th August 2013) - Meerschaert, Mark M.; Dogan, Mine; Van Dam, Remke L.; Hyndman, David W.; Benson, David A.
Abstract : [1] Hydraulic conductivity ( K ) fields are used to parameterize groundwater flow and transport models. Numerical simulations require a detailed representation of the K field, synthesized to interpolate between available data. Several recent studies introduced high‐resolution K data (HRK) at the Macro Dispersion Experiment (MADE) site, and used ground‐penetrating radar (GPR) to delineate the main structural features of the aquifer. This paper describes a statistical analysis of these data, and the implications for K field modeling in alluvial aquifers. Two striking observations have emerged from this analysis. The first is that a simple fractional difference filter can have a profound effect on data histograms, organizing non‐Gaussian ln K data into a coherent distribution. The second is that using GPR facies allows us to reproduce the significantly non‐Gaussian shape seen in real HRK data profiles, using a simulated Gaussian ln K field in each facies. This illuminates a current controversy in the literature, between those who favor Gaussian ln K models, and those who observe non‐Gaussian ln K fields. Both camps are correct, but at different scales. Key Points: Fractional differencing is necessary to remove correlations from HRK data GPR is very useful to determine facies boundaries Combining Gaussian facies reproduces the non‐Gaussian profiles seen in real data